Style in Non-Fiction Books: The Subtle Art of Not Giving a F*ck by Mark Manson - Daud, Rolan K.; Hinta, Ellyana; Didipu, Herman (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
The Subtle Art of Not Giving a F*ck by Mark Manson is a popular non-fiction work that conveys life messages in an honest, assertive, and sarcastic manner. This study aims to describe the style of language in the book from three aspects: word choice, tone, and sentence structure. The study uses a qualitative descriptive method with qualitative analysis. Data was collected through a literature review of the book, then analysed through the stages of data condensation, data presentation, and conclusion drawing. The theoretical framework refers to Gorys Keraf's concept of language style, which includes classification based on word choice (formal, informal, conversational), tone (simple, noble, middle), and sentence structure (climax, anticlimax, repetition, parallelism, antithesis). The results of the study shed light that the sentence structure aspect is the most dominant with 35 data points, followed by word choice (33 data points) and tone (30 data points). The word choice tends to be straightforward and reflective, the tone is casual yet serious, while the sentence structure is used strategically to reinforce the message and emotion. These findings indicate that style is the author's main tool in conveying ideas effectively and communicatively. The distinctive style, which is direct, straightforward, and full of honesty, makes it easier for readers to understand and resonate with the reflective messages in this book. This study is expected to serve as a reference in the study of language style in popular non-fiction texts.